Úloha viscerální tukové tkáně v etiopatogenesi metabolického syndromu sledovaná na úrovni molekulárně genetických charakteristik tkáně - Štich, Vladimír (Iga MZ ČR, 2007)
The aim of the project is to bring a contribution for understanding the role of visceral adipose tissue to pathogenesis of metabolic syndrome. Molecular genetic characteristics of visceral and subcutaneous adipose tissue will be investigated Attention will be paid to the genes supposed to play a role in pathogenesis of insulin resistence and metabolic syndrome: 1. genes involved in regulation of lipolysis and non-esterified fatty acids release 2. genes encoding synthesis of cytokines The gene expressionwill be investigated in women with signs of metabolic syndrome (n=15) and in a control group (n=15). The samples of adipose tissue will be obtained during diagnostic laparoscopy indicated to the subjects for gynecological reasons Phenotypic characteristics of subjects will include hormonal and metabolic laboratory indices, indices of insulin resistence, body composition, energy metabolism. Levels of mRNA will be measured using real-time PCR and microarray methods
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Gene Expression; metabolický syndrom; inzulinová rezistence; endokrinologie; Gene Expression Regulation; vnitřní lékařství; biologie; tuková tkáň; cytokiny; Genital Diseases, Female; Adipose Tissue; laparoskopie; exprese genu; gynekologie a porodnictví; gynekologická onemocnění; lipolýza; Lipolysis; Laparoscopy; Metabolic Syndrome; regulace genové exprese; Cytokines; Insulin Resistance